EDUKASI POLA HIDUP BERSIH DAN SEHAT SERTA PENERAPAN ADAPTASI KEBIASAAN BARU PASCA PANDEMI COVID19 - Saipul Al Sukri; Zulfahmi Zulfahmi; Irfan Ridha; Abdiana Ilosa; Zulhaida Zulhaida; Nurrahmi Hayani; Rahmadeni Rahmadeni; Darni Darni; Hakmi Wahyudi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
E-Warong Berkah Harapan is one of the places where the SEMBAKO program aid packages are distributed, which serves nearly 400 aid recipients every month. The crowd that occurred was not impossible to cause a new transmission clutser for Covid19. Therefore, the service team from UIN Sultan Syarif Kasim conducted counseling on